Shifts in Biotechnology Research Fronts 2000–2026: A Bibliometric Study of Topic Emergence and Citation Landscapes - Judijanto, Loso (Westscience Press, 2026)
This study aims to examine the evolution of biotechnology research from 2000 to 2026 by employing a bibliometric approach to identify emerging topics and analyze citation landscapes. Data were collected from the Scopus database and analyzed using VOSviewer to explore keyword co-occurrence, co-citation patterns, and temporal developments. The findings reveal that biotechnology research has undergone a significant transformation from a focus on molecular biology and laboratory-based studies toward more interdisciplinary, application-driven, and sustainability-oriented domains. Core research themes such as human biology, metabolism, and biochemical processes remain central, while emerging topics—including microbial systems, biodegradation, bioenergy, and sustainable development—highlight the field’s alignment with global environmental and technological challenges. Citation analysis further indicates a shift from foundational theoretical work to innovation-focused and application-oriented research fronts. The study also demonstrates increasing convergence between biotechnology and other disciplines, such as chemistry, nanotechnology, and computational sciences.